Multi-gene analysis of the Russula crown clade (Russulales, Basidiomycota) revealed six new species and Alboflavinae subsect. nov. from Fagaceae forests in China - Niu, Caiyun; Liu, Tiezhi; Zhao, Shiyi; Ren, Jing; Zhao, Yi; Kang, Xia; Qin, Weiqiang; Xie, Xuejiao; Zhang, Xu; Wei, Tiezheng; Tian, Jinghua; Li, Xiao; et al. (Frontiers in Plant Science, 2024)
Introduction The crown clade is one of two major groups in the Russula subg. Russula. Methods/material An analysis of Chinese samples was performed based on the morphology, internal transcribed spacer (ITS) sequences, and multi-gene phylogenies of 28S nrLSU, 16S mtSSU, rpb1, rpb2, and tef1-α. Results The results supported the independence of six new species: Russula alboflava (sect. Amethystinae), R. chrysantha (subsect. Chamaeleontinae), R. liyui (subsect. Laricinae), R. lutescens (subsect. Olivaceinae), R. paraxerampelina, and R. prunicolor (subsect. Xerampelinae) from Fagaceae forest habitats. Subsect. Alboflavinae was newly proposed in sect. Amethystinae. Members of the new subsection include R. alboflava, R. burlinghamiae, and possibly R. ballouii. Discussion Our analyses also supported the claim that two species of R. fulvograminea (subsect. Laricinae) and R. subrubens (subsect. Xerampelinae) have a Eurasian distribution. The habitat and primary hosts of the main phylogenetic clades within related subsections were summarized and discussed.